pengembangan e LKPD model Problem Based Learning pada usaha dan energi untuk meningkatkan kemampuan kognitif fisika peserta didik ditinjau dari representasi matematis dan representasi verbal - Nunung Setiati; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this study is to develop an e worksheet that refers to a competent and effective problem-based learning model. The method of this study is RnD (Research and Development). This study includes a development study using a 4D development model (Define, Design, Develop, and Dissiminate). The product of this study is the e worksheet problem-based learning model. High school teachers validate learning tools with three practical validators. Subjects were class X students in mathematics and natural science public high school 1 Baturetno. The results showed that 1) the e worksheet problem-based learning model was included in the valid category, 2) the e worksheet problem-based learning model was used effectively in e-learning